2015
DOI: 10.1155/2015/824395
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of Bicarbonate-Rich Mineral Water Improves Glycemic Control

Abstract: Hot spring water and natural mineral water have been therapeutically used to prevent or improve various diseases. Specifically, consumption of bicarbonate-rich mineral water (BMW) has been reported to prevent or improve type 2 diabetes (T2D) in humans. However, the molecular mechanisms of the beneficial effects behind mineral water consumption remain unclear. To elucidate the molecular level effects of BMW consumption on glycemic control, blood metabolome analysis and fecal microbiome analysis were applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 35 publications
1
72
1
Order By: Relevance
“…An association of MW with longevity, however, has not been concerned and investigated until currently. Even though it was proven that Nagoya hot MW (Takeda, Oita, Japan) can enrich the lean-related bacterial family, Christensenellaceae [17], no correlation of hot MW with lifespan has been explored up to now. By focused on the waterborne microbes, we disclosed for the first time that SSB/MEB and SRB are decreased in CS-BC+MW mice, but increased in CS-BC mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association of MW with longevity, however, has not been concerned and investigated until currently. Even though it was proven that Nagoya hot MW (Takeda, Oita, Japan) can enrich the lean-related bacterial family, Christensenellaceae [17], no correlation of hot MW with lifespan has been explored up to now. By focused on the waterborne microbes, we disclosed for the first time that SSB/MEB and SRB are decreased in CS-BC+MW mice, but increased in CS-BC mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that transplantation of Christensenella minutia to germ-free mice can reduce weight gain. Moreover, the abundance of Dehalobacteriaceae that are increased after MW drinking were found to positively correlate the abundance of Christensenellaceae [17].…”
Section: Introductionmentioning
confidence: 92%
“…Table 4: RCTs comparing low mineralized with bicarbonate-rich water (five studies); [25][26][27][28][29]. Table 5: RCTs comparing low mineralized with bicarbonate-and magnesium-rich water (two studies); [16,30].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…A further seven studies compared different types of water, all low mineralized with bicarbonate-rich water (879-2946 mg/L), five of them with low [25][26][27][28][29] and two [16,17,30] with high concentrations of magnesium (102 and 291 mg/L) ( Tables 4 and 5); three studies compared uncarbonated water [16,28,30], two studies carbonated water [27,29] and two studies carbonated bicarbonate-rich water versus uncarbonated mineral water [25,26].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation